La naturaleza del verbo de las colocaciones verbonominales con 'dar' - Bustos Plaza, Alberto (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
It has often been stated that Spanish combinations such as dar un beso ('to give a kiss'), dar un paseo ('take a walk') etc. contain a grammaticalized verb whose function consists in conjugating an abstract noun. A comparison with the equivalent Latin combinations does not provide any evidence of the hypothesized grammaticalization process. The grammatical status of the verb is not confirmed either by parameters such as Lehmann's (1985, 1995). Those are reasons to reconsider the hypothesis of the grammaticalization of this verb
The nature of the verbs of the verbo-nominal combinations with 'dar'